If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(p + -1) = 3p + 2 Reorder the terms: 2(-1 + p) = 3p + 2 (-1 * 2 + p * 2) = 3p + 2 (-2 + 2p) = 3p + 2 Reorder the terms: -2 + 2p = 2 + 3p Solving -2 + 2p = 2 + 3p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-3p' to each side of the equation. -2 + 2p + -3p = 2 + 3p + -3p Combine like terms: 2p + -3p = -1p -2 + -1p = 2 + 3p + -3p Combine like terms: 3p + -3p = 0 -2 + -1p = 2 + 0 -2 + -1p = 2 Add '2' to each side of the equation. -2 + 2 + -1p = 2 + 2 Combine like terms: -2 + 2 = 0 0 + -1p = 2 + 2 -1p = 2 + 2 Combine like terms: 2 + 2 = 4 -1p = 4 Divide each side by '-1'. p = -4 Simplifying p = -4
| y=1/3(-2)-2 | | y=1/3(2)-2 | | z^2-4z-8=0 | | 4x-4=2x-34 | | y=-2(-3)-8 | | -10x^2+9x+9= | | 7/12x=35 | | 3x+7=-2-8 | | 2r-6=8 | | 4x^2-25x+25= | | (x-9)2=49 | | -3(5x+12)=-18x-15 | | -1924*x=-962 | | .05x+.04y=119 | | .05x+.04y=252 | | 0.2x^2+4x-6=0 | | -2x^2+20x-48= | | -2t+2x=9 | | 3(g-5)=2(q+5) | | 1547=1234+h | | 3ax^2-27a=0 | | a=b+bedforc | | 9-3y=-15 | | 20(x+.28)=23(x) | | y^2+15y+50=0 | | xy-2y^2+4x^2=66 | | y=7-2 | | 7(-7)-2y=-14 | | 7(-7)-2y=14 | | 3x+11=55 | | 7(-14)-2y=-14 | | -3862*x=-1931 |